The Statues of Job Enrichment among Public School Principals in Hebron Governorate from the teachers' point of view - Awawdeh, Tagreed Yaser; Abu Khayran, Ashraf Mohammad (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the status of Job Enrichment among public school principals in Hebron Governorate from the teachers' point of view. The sample study was a stratified random sample of (689) individuals. Which is (7.0%) of the study population. The researcher used the questionnaire as a tool for her study، and it consisted of (41) items distributed over five domains. The study questions were answered and the hypotheses were tested using the statistical package for social behavior (SPSS).The results of the study showed that the estimates of the study sample of the status of job enrichment among the principals of public schools in Hebron Governorate came with a high degree for all areas of the study tool، Where the arithmetic mean of the total domains was (3.6) and the total standard deviation was (0.61)، and all domains came with a average score as well. (Feedback, task identification, importance of tasks, diversity of tasks, independence) in order of average. the results also showed that there were statistically significant differences between the average estimates of the study sample of the status of job enrichment among the principals of public schools in Hebron Governorate, due to the two variables (specialization، Years of Experience). While the results did not show that there were statistically significant differences،due to the variables (Gender, directorate). In light of the results, the researcher recommended to creating an educational environment suitable for principals performance, and providing professional development opportunities for principals.
Keywords: Job Enrichment; School Principals; Hebron Governorate